O evangelho segundo o McDonald's: estudo sobre o processo de produção da fast-food - Alves, Carmen Lucia Rodrigues (2006)
This study approaches the production process of McDonald´s fast food chain, recovering the way their meals are produced, the technology invested on them, the definitions about color, scent, taste, as well as the labor relations, from worker´s functional structure, to employees´ selection and training in order to allow them to accomplish all functions that substantiate the production process. By analysing McDonald´s products advertising, this study also focus on the ideology it diffuses, particularly due to the fact that McDonald´s is a fast food chain of global extent